A dynamic event-triggered approach to observer-based PID security control subject to deception attacks. (October 2020) - Zhao, Di; Wang, Zidong; Wei, Guoliang; Han, Qing-Long
Abstract: In this paper, the observer-based PID security control problem is investigated for a class of linear discrete-time systems subject to deception attacks. A new index for security level is proposed to account for the effect of the randomly occurring deception attack on the closed-loop system. A dynamic event-triggered mechanism, whose threshold parameter is dynamically adjusted according to a certain rule, is exploited to modulate the transmission of data packets with hope to effectively alleviate unnecessary energy consumption. Sufficient conditions for the existence of the expected observer-based PID controller are presented to ensure the input-to-state stability of the closed-loop system while achieving the prescribed security index. Gain matrices of the desired PID controller are parameterized in terms of the solutions to certain matrix inequalities that are readily solvable. Finally, a simulation example is given to verify the effectiveness and advantages of the developed controller design approach.